Pengaruh Service Quality Terhadap Customer Loyalty Melaui Customer Satisfaction Pelanggan Jawa Pos Radar Jember - Narto; Suwignyo Widagdo; Agustin Hari Prastyowati (RELASI : JURNAL EKONOMI, 2020)
For print media, maintaining and adding customers is very important in today's digital era. Including Jawa Pos Radar Jember. Companies must improve Service Quality (service quality), to create and maintain Customer Loyalty (loyal customers). This research is quantitative descriptive. This study was conducted on Jawa Pos Radar Jember customers in Jember Regency, precisely in Sumbersari, Patrang and Kaliwates Regencies. Data collection techniques by observation, questionnaire and direct interview. The number of samples was 125 out of a population of around 7,500 subscribers to the Jawa Pos Radar Jember newspaper. This study uses Service Quality independent variables (Tangibility, Reliability, Responsiveness, Assurance, Empathy), Customer Satisfaction variablesand Customer Loyalty dependent variables. The analytical method used is multiple regression analysis with path analysis, classic assumption test (multicollinearity test, heteroscedasticity test, and normality test).The purpose of this study is 1) to testand analyze Reliability, Responsiveness, Assurance, Empathy effect on Customer Satisfaction and Customer Loyalty. 2) Test and analyze the moderation of Customer Satisfaction against Customer Loyalty.The results show that Tangibility, Responsiveness, Assurance, Empathy has no significant effect on Customer Satisfaction. Only reliability has a significant effect on Customer Satisfaction. Conversely, Reliabilty, Responsiveness, Assurance, Empathy has a significant effect on Customer Loyalty. Only, Tangibility is not a significant effect on Customer Loyalty. AndCustomer Saticfaction does not become intervening between Service Quality and Customer Loyalty Keywords: Service Quality, Customer Satisfaction dan Customer Loyalty